Peningkatan Mutu Organoleptik Keripik Pisang Produksi Kelompok Wanita Tani di Desa Neglasari - Afifah Nurmaimanah; Prayoga Suryadharma (Jurnal Pusat Inovasi Masyarakat (PIM), 2020)
Farmer Women Group, or known as KWT, is one of the groups engaged in processing post-harvest products. There are 4 main products produced by KWT, namely cassava chips, banana chips, pikong, and candied nutmeg. The biggest production is banana chips. The problem with "Miraos Snack" banana chips is that the demand for "Miraos Snack" banana chips is still low. The low selling power of banana chips is due to the low organoleptic quality of banana chips in the form of a less crisp texture, a sense of sepat and bitter, having a blackish brown color on the edges of the banana chips so that this can reduce the acceptance of quality from consumers and in terms of taste variants are less varied, only original taste. Soaking with a solution of betel lime produces banana chips KWT has a crisp texture, durable, not brown, and does not have a sense of sepat, bitter or distorted. To add to the flavor variants of banana chips, a training was made in making chocolate spices and spicy flavors that can improve the quality of organoleptics and also increase the flavor flavors of Miraos Snack banana chips ". Based on the results of processing banana chips by directing LPPM IPB produced good quality banana chips that have normal colors and odors, crispy textures, and banana-specific flavors mixed with chocolate flavors for variations of chocolate-flavored chips and banana-specific flavors mixed with spicy chili flavors for variants spicy taste. KWT was pleased and applied the results of the training from LPPM to their banana chip products and then they sold to the market. Keywords: banana chips, organoleptic quality, Women Farmers Group (WFG)